In vivo evaluation of oxidized multiwalled-carbon nanotubes-mediated hyperthermia treatment for breast cancer - Muhammad Redza, Mohd Radzi; Nur Amanina, Johari; Wan Fatin Amira, Wan Mohd Zawawi; Nurliyana, Ahmad Zawawi; Nurriza, Ab. Latiff; Nik Ahmad Nizam, Nik Malek; Asnida, Abdul Wahab; Maheza Irna, Salim; Khairunadwa, Jemon (Elsevier B.V., 2022)
Breast cancer is one of the most common types of cancer that contribute to high mortality worldwide. Hyperthermia (HT) was introduced as one of the alternative treatments to treat breast cancer but has major drawback of damaging normal adjacent cells. This study explores the integration effect of multiwalled‑carbon nanotubes (MWCNTs) in combination with hyperthermia treatment for breast cancer therapy regimes. In this study, acid-functionalized MWCNTs (ox-MWCNTs) were prepared by acid washing methods using H2SO4/HNO3 (98%/68%) with the ratio of 3:1 (ν/ν) and characterized by colloidal dispersibility test, FTIR, TGA, XRD, FESEM and EDX analysis. EMT6 tumor-bearing mice were treated with ox-MWCNTs in combination with local HT at 43 °C. The tumor progression was monitored and the influence of immune response was evaluated. Results from this study demonstrated that mice from ox-MWCNTs in combination with local HT treatment group experienced complete tumor eradication, accompanied by a significant increase in median survival of the mice. Histological and immunohistochemical analysis of tumor tissues revealed that tumor treated with combined treatment underwent cell necrosis and there was a significant reduction of proliferating cells when compared to the untreated tumor. This observation is also accompanied with an increase in Hsp70 expression in tumor treated with HT. Flow cytometry analysis of the draining lymph nodes showed an increase in dendritic cells infiltration and maturation in mice treated with combined treatment. In addition, a significant increase of tumor-infiltrated CD8+ and CD4+ T cells along with macrophages and natural killer cells was observed in tumor treated with combined treatment. Altogether, results presented in this study suggested the potential of ox-MWCNTs-mediated HT as an anticancer therapeutic agent, hence might be beneficial in the future of breast cancer treatment.